EFEKTIVITAS PERAN BADAN PENYELESAIAN SENGKETA KONSUMEN DALAM MENYELESAIKAN PENGADUAN KONSUMEN - Abdul Rahman; Asma; Maemanah (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
The amendment to the 1945 Constitution affirmed the supremacy of the constitution, giving birth to auxiliary state institutions such as BPSK to maintain a balance between consumers and business actors. BPSK exists as an alternative to non-litigation dispute resolution that is cheap, fast, and fair, in order to ensure consumer protection through mediation, conciliation, or arbitration mechanisms. To analyze the effectiveness of consumer dispute resolution by the Consumer Dispute Resolution Agency and to review and analyze the legal obstacles faced by the Consumer Dispute Resolution Agency in carrying out consumer protection duties. This research is a normative legal research using a statutory approach and a conceptual approach. The effectiveness of BPSK was determined by regulatory clarity, infrastructure availability, quality of human resources, and public legal awareness. Normatively, BPSK has legitimacy through the UUPK and the Ministry of Industry, but there are still contradictions, especially regarding the nature of the decision that is called final but can still be objected to the District Court.